Effect of inoculum spraying on rice (Oryza sativa) residue decomposition kinetics - REKHA; DEVRAM, LANDE SATISH; SHUKLA, LIVLEEN; MANI, INDRA; PARRAY, ROAF A; DAS, SUKANTA; CHOBHE, KAPIL A; KUMAR, RAJEEV; KHURA, TAPAN K (The Indian Journal of Agricultural Sciences, 2022)
Rice (Oryza sativa L.) residues on Indian farms have remained a major challenge due to its voluminous and unmanageable quantity and short window for sowing successive crops. A study was carried out at research farm of the ICAR-Indian Agricultural Research Institute, New Delhi during 2019–21, to develop a microbial inoculum spraying system for efficient decomposition of rice residues. The study involved the evaluation of flood nozzles at different operational parameters like operating pressure (1.5, 2.5 and 3.5 kg/cm2), nozzle heights (50, 60 and 70 cm) and forward speeds (2.5 and 3 km/h). The inoculum spray was characterized in terms of Volume Median Diameter (VMD), Number Median Diameter (NMD) and Droplet Density (DD). The decomposition kinetics was studied in terms of total organic carbon, total nitrogen, phosphorus, potassium and N-acetyl glucosamine observed at an interval of 10 days and 20 days after inoculums application. VMD and NMD were found in the range of 347–243 μm and 77.67–87.8 μm respectively, whereas droplet density ranging from 252.5–403.9 droplets/cm2 to spray microbial inoculum using flood nozzle. The C:N ratio of rice residue was reduced by 19.96% and 36.77% respectively after 10 and 20 days of rice residue decomposition compared to control. Carbon content reduced from 47.98–41.24% and total nitrogen content increased from 0.532–0.728 % after 20 days of decomposition. The N-acetyl glucosamine content of rice residue increased from 0.77–3.53 mg/g after 20 days indicating that target-oriented microbial inoculum spraying accelerates the decomposition kinetics of rice residues.